2021
DOI: 10.3126/ajms.v12i5.34453
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality profile of children admitted in pediatric department – A single center study

Abstract: Back ground: Child morbidity and mortality is an issue of great concern for policy makers because in spite of good efforts still less than 5 years mortality rate is very high and many babies could not survive beyond infancy. Majority of pediatric deaths occurred due to preventable and treatable causes. An emphasis needed on early diagnosis and timely interventions in pediatric patients associated with high risk factors. Aims and Objectives: To study clinical spectrum, morbidity and mortality profile in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Similar findings were found in the study conducted by Joshi, et al 12 and others. 13 , 14 This could be due to higher acceptance of parents to admit their sons compared to their daughters 15 but could also be due to the variable gender composition of the study population. 1…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar findings were found in the study conducted by Joshi, et al 12 and others. 13 , 14 This could be due to higher acceptance of parents to admit their sons compared to their daughters 15 but could also be due to the variable gender composition of the study population. 1…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings were found in the study conducted by Joshi, et al 12 and others. 13,14 This could be due to higher acceptance of parents to admit their sons compared to their daughters 15 but could also be due to the variable gender composition of the study population. 1 The study also found that most of the children stayed in hospital for 2-7 days (83%), followed by those who were discharged after 1 day (11%).…”
Section: Discussionmentioning
confidence: 99%
“…First, malnutrition causes 3.5 million deaths worldwide and is responsible for 35% of morbidities in children under five [54]. undernutrition is, among other things, a source of anorexia [55], of the decline of intellectual coefficient, vulnerability of diseases [56] and severe anemia [57]. Malnutrition suffered in utero and in early childhood increases the risk of obesity and chronic non-communicable diseases in adulthood [58].…”
Section: Consequences Of Undernutritionmentioning
confidence: 99%